The Detector of the Quality of Ripeness of Gondang Sweet Guava Fruit in Jombang - Miftachul Chusnah; Mohammad Sifa’ Dian Ramadhani (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
In this modern era, many modern tools are used in daily activities, especially in terms of selling fruit, actually in terms of selecting the quality of fruit on a large scale which in this case still uses the old method, which is only using the human sense of sight and smell system. In this problem, a system for detecting the quality of fruit maturity levels is made digitally where the system detects fruit that can be used on a large or large scale by using a sensor device and then displayed on an LCD using Arduino Uno as the brain of the system and TCS3200 sensors and large-sized LCDs. 16x2 ple i2c.